Investigating the Impact of Subsidy Revenues on Turnover at the Level of Agriculture, Forestry and Fishing Companies in the Coastal Area of the Black Sea - Kamer-Ainur AIVAZ (Dunarea de Jos University of Galati, 2021)
In Constanta County, the fields of fishing, agriculture and forestry have greatly transformed, as far as their situation in the national economy and their importance in maritime spatial planning is concerned. This paper seeks to quantify the impact on turnover of the subsidies granted to this sector of national economy over a ten-year span. Although the strong statistical link between the evolution of turnover and the volume of granted subsidies may be slightly predictable, the dimension of these links and the subsidies’ impact on the interest in developing new agricultural activities and the ability to obtain operating profits point out some peculiarities depending on the sub-activities carried out in Romania. The importance of the study is also increased by the comparative analysis that tackled the development of several successful businesses dealing with certain types of agricultural activities and the progress of the subsidies’ value.